Role of rectal myomectomy in refractory chronic constipation - Rajeev G Redkar; Pankaj K Mishra; Chandralekha Thampi; Shachi Mishra (Wolters Kluwer Medknow Publications, 2012)
Background: To assess the role of diagnostic and therapeutic value of anorectal myectomy in cases of chronic refractory constipation. Materials and Methods: Twenty-eight patients 11 months to 9 years of age presenting with chronic constipation, with contrast enema showing dilated rectum and sigmoid colon were included in the study. Anorectal myectomy under general anaesthesia was carried out in these selected patients and were followed-up for up to 6 months to 5 years. Clinical improvement was measured by post-operative bowel habits and relief of symptoms. Results: Twenty-two patients improved clinically; partial response in 4 patients, no response in 2 patients. Two patient required further pull through surgery and was found to have transition zone at the recto-sigmoid level. Ten patients had aganglionosis (of which 5 had ganglion cells present in the proximal part of speciment), 7 had normal histology, 7 had hypoganglionosis, 2 had intestinal neuronal dysplasia, one had nerve hypertrophy and one had immature ganglia. Conclusion: Anorectal myectomy is an effective and technically simple procedure in selected patients with chronic refractory constipation, for both diagnostic and therapeutic purpose. Because apart from confirming Hirschsprung's disease, it also therapeutically relieves symptoms in 93% of patients with chronic refractory constipation.